The temperature dependence of optical properties of tungsten in the visible and near-infrared domains: an experimental and theoretical study. (20th October 2017) - Minissale, Marco; Pardanaud, Cedric; Bisson, Régis; Gallais, Laurent
Abstract: The knowledge of optical properties of tungsten at high temperatures is of crucial importance in fields such as nuclear fusion and aerospace applications. The optical properties of tungsten are well known at room temperature, but little has been done at temperatures between 300 K and 1000 K in the visible and near-infrared domains. Here, we investigate the temperature dependence of tungsten reflectivity from the ambient to high temperatures (<1000 K) in the 500–1050 nm spectral range, a region where interband transitions make a strong contribution. Experimental measurements, performed via a spectroscopic system coupled with laser remote heating, show that tungsten's reflectivity increases with temperature and wavelength. We have described these dependences through a Fresnel and two Lorentz–Drude models. The Fresnel model accurately reproduces the experimental curve at a given temperature, but it is able to simulate the temperature dependency of reflectivity only thanks to an ad hoc choice of temperature formulae for the refractive indexes. Thus, a less empirical approach, based on Lorentz–Drude models, is preferred to describe the interaction of light and charge carriers in the solid. The first Lorentz–Drude model, which includes a temperature dependency on intraband transitions, fits experimental results only qualitatively. The second Lorentz–Drude model includes in addition a temperature dependency on interband transitions. It is able to reproduce the experimental results quantitatively, highlighting a non-trivial dependence of interband transitions as a function of temperature. Eventually, we use these temperature dependent Lorentz–Drude models to evaluate the total emissivity of tungsten from 300 K to 3500 K, and we compare our experimental and theoretical findings with previous results.